The Polar Eskimo population, Thule District, North Greenland. - Gilberg, Rolf (Meddelelser om Grønland, 1976)
The Polar Eskimo society developed during the 20th Century from a small, self-sufficient hunting society into a large, primarily hunting society dependent on supplies from the outside world. As a result of outside influences, in the 1950's and 1960's the Polar Eskimo population doubled from three hundred to over six hundred individuals. Diagrams and tables included in this paper give a to some extent detailed picture of the changes which took place, and the development of the Polar Eskimo population from 1893 to 1973 is treated in some detail. Special attention is given to developments in 1969.